The influence of performance expectancy, effort expectancy, and social influence on behavioral intention to use ShopeePay - Ustiza Risman; Astra Prima Budiarti (Universitas Negeri Padang, 2023)
The purpose of this study is to analyze the dimensions of Performance Expectancy, Effort Expectancy and Social Influence on Behavioral Intention to Use mediated by Trust on the ShopeePay e-wallet in Padang City. The population used in this study are all consumers who have used ShopeePay in Padang City. There were 200 responders in the study's samples. Online questionnaires were used to collect data, and sophisticated PLS (Partial Least Square) software was used to process the data. The analysis of the data revealed the following: (1) Performance expectancy has a favorable and considerable impact on consumers' trust in ShopeePay. (2) The trust of ShopeePay consumers is positively and significantly impacted by effort expectation. (3) Social Influence has a favorable and considerable impact on consumers' trust in ShopeePay. (4) The behavioral intention to use ShopeePay is positively and significantly impacted by trust. (5) Performance expectancy, which is mediated by trust, has a favorable and significant impact on behavioral intention to use ShopeePay. (6) The behavioral intention to use ShopeePay is positively and significantly influenced by effort expectancy, which is mediated by trust. (7) The behavioral intention to use ShopeePay is significantly and favorably influenced by social influence, which is mediated by trust.